Development of a squamous cell carcinoma mouse model for immunotoxicity testing. (3rd March 2016) - Sominski, Devon D.; Rafferty, Patricia; Brosnan, Kerry; Volk, Amy; Walker, Mindi; Capaldi, Dorie; Emmell, Eva; Johnson, Kjell; Weinstock, Daniel
Abstract: An important component of safety assessment of new pharmaceuticals is evaluation of their potential to increase the risk of developing cancer in humans. The traditional 2-year rodent bioassay often is not feasible or scientifically applicable for evaluation of biotherapeutics. Additionally, it has poor predictive value for non-genotoxic immunosuppressive compounds. Thus, there is a need for alternative testing strategies. A novel 3-stage tumor model in syngeneic C3H/HeN mice was evaluated here to study the effects of immunosuppressive drugs on tumor promotion and progression in vivo . The model employed a skin squamous cell carcinoma cell line (SCC VII) due to the increased prevalence of squamous cell carcinoma (SCC) in humans associated with immunosuppression after transplants. Local invasion, colonization and tumor progression were evaluated. The validation set of immunosuppressive drugs included: Cyclosporin (CSA), cyclophosphamide (CTX), azathioprine, etanercept, abatacept and prednisone. Local invasion was evaluated by histological assessment as well as fluorescence trafficking from Qdot®-labeled tumor cells from the site of inoculation to the draining lymph node. Colonization was evaluated by lung colony counts following intravenous inoculation. Tumor progression was assessed by morphometric analysis of lesion area, angiogenesis and growth fraction of established metastatic neoplasia. Immunosuppressive drugs in the validation set yielded mixed results, including decreased progression. The methods and results described herein using an in vivo syngeneic mouse tumor model can provide insight about the assessment of immunosuppressive drugs in carcinogenicity risk assessment.